Unraveling the Effect of Soil Moisture on Microbial Diversity and Enzymatic Activity in Agricultural Soils - Kalisa Amarsingh Bogati; Piotr Sewerniak; Maciej Walczak (Microorganisms)
This study investigates the impact of two months of drought stress on the microbial diversity, enzyme activities and functional diversity in four agricultural soils (Gniewkowo (G); Lulkowo (L); Nieszawa (N); Suchatówka (S)) from Poland during summer season. The physicochemical parameters (pH, organic carbon, calcium carbonate, total nitrogen, nitrate, ammonium, total phosphorus and available phosphate), microbial abundance, community-level physiological profiling, and soil enzymes (acid and alkaline phosphatases, dehydrogenase and urease) were investigated at two time intervals: zero-week (T0) and the eighth week (T8). Generally, microbial enumeration showed higher bacterial populations (496.63 × 104 CFU g−1 dry soil) compared to actinomycetes (13.43 × 104 CFU g−1 dry soil), and the fungal population was the lowest (67.68 × 102 CFU g−1 dry soil) at T8. Functional diversity showed a strong, statistically significant positive effect in the G, N and S sites at T8. Acidobacteriota and Actinobacteriota declined in most places, while Firmicutes, Crenarchaeota and drought-tolerant bacteria such as Gemmatimonadota exhibited resistance. The fungal communities showed site-specific responses, with an increase in drought-tolerant Mortierellomycota and Chytridiomycota and a decrease in Ascomycota and Basidiomycota, suggesting possible adaptability. Overall, the microbial populations, enzyme activity, and functional diversity were positively correlated with soil moisture content across all four investigated sites. The significance of organic matter, soil structure, and moisture retention in determining microbial resilience to drought is underscored by these changes in microbial diversity and function, which in turn affect nutrient cycling and soil ecosystem stability. The findings of our study indicate that soil biological activities in agricultural regions can be modified by a mere two months of drought.